CONGRATULATING IN BRITISH AND VIETNAMESE CULTURES = Cách thức chúc mừng trong văn hóa Anh và văn hóa Việt - Vũ, Thị Phương Thanh (2020)
One of the biggest obstacles in the intercultural communication is the lack of cultural knowledge which may lead to misunderstandings and even communication breakdown. Based on the theoretical background of cross-cultural communication, the study sought to investigate the similarities and differences in congratulating in British and Vietnamese cultures. The factors affecting the informants’ responses such as gender, age, the relative power and social distance with the communicating partners were taken into consideration. Discourse Completion Task (DCT) was employed as the main data collection instrument to elicit the verbal congratulations made by 30 British and 30 Vietnamese native people. The three most popular situations concerning congratulating were described in each survey questionnaire. In each situation, the participants had to deal with six different interlocutors. During the process of research analysis, some informal interviews with two groups of participants were conducted to collect more information and explanation for their responses. It was discovered that British and Vietnamese participants used a variety of strategies and expressed dissimilar preference for those strategies in different situations, with various informants’ and communicating partners’ parameters. The conclusion drawn from data analysis and findings, and the recommendations for further study were presented in a brief and concise way. The study was expected to partially fill the gap of intercultural communication between British and Vietnamese cultures so as to help people from two cultures avoid cultural shock and communicating breakdown. It was also hoped to support those who interested in the research topic and especially ULIS students as the potential intercultural communicators in the coming time.